Ländliche Neusiedlung im Gebiet der Bundesrepublik Deutschland vom Ende des 19. Jahrhunderts bis zur Gegenwart - Graafen, Rainer (ERDKUNDE, 1986)
At the end of the last century renewed rural colonization in the area of the present Federal Republic first began in the former Prussian provinces, particularly in Schleswig Holstein and Province of Hanover. A characteristic feature of the time which persisted until 1918 was the setting up of leasehold farms by public general commissions and private settlement societies. Initially the settlers would take their farms on lease, but they had the option of becoming owners of their farms by making regular payments of a fixed rent over a period of several decades. Cultivated areas of moor and heath, as well as land sold by large estates, were the principal sources of land for colonization. In the early years of the Weimar Republic a large number of laws for the acceleration of new rural colonization were passed. As a result of the unstable economic situation, however, few farms were actually able to take off in the period up to 1924; after the currency reform, on the other hand, especially in the time from1927 to 1931, a great deal of colonization took place. In1933 Hitler relieved the Lander of the control over rural colonization and made it part of the national regional policy, which included the entire area of the empire. New rural colonization was to be carried out with special attention to the principle of central places, which Christaller had introduced into regional policy. After World War II a flood of more than10 million refugees and dispossessed (including about 300,000 farming families and an equal number of families of agricultural workers) from the former German territories in the east poured into the area occupied by the three western Allied Powers. The setting up of new farms did not only take place in the moor and heath regions of Schleswig-Holstein, Lower Saxony and Bavaria, but also in the area of the central uplands, where very little new colonization had taken place up to 1945.